Sociopolitical Dimensions of Mathematics Education From the Margin to Mainstream (ICME-13 Monographs,, 2018)
This book documents and expands on the diverse social and political dimensions of mathematics education issues, concerns, perspectives, contexts, and approaches presented in Topic Study Group 34 of the 13thInternational Congress on Mathematical Education (ICME 13). The book also argues for and promotes the mainstreaming of the sociopolitical dimensions of mathematics education through an ongoing critique and inquiry into content, policies, practices and theories. Accordingly, the main theme throughout the book is captured and illuminated by bringing voices from the margin to the mainstream. In this respect it is both an aspirational and a reality, as evidenced by the increasing references to the sociopolitical dimensions in o1`ther areas of mathematics education-for example, in several of the plenary presentations at the ICME 13. The authors have reflected on their ideas with a view to orienting and enhancing research in the sociopolitical dimensions of mathematics education that is grounded in current education systems within their specific sociocultural contexts.